Factors affecting outpatient bowel preparation for colonoscopy - Saloni A. Shah; Elinor Zhou; Neil D. Parikh (Society of Gastrointestinal Intervention, 2019)
Background : Colonoscopy remains one of the most effective methods to screen for colorectal cancer. However, the detection of colorectal polyps is dependent on the cleanliness of the colonic tract. The purpose of our retrospective chart review was to identify clinical factors that were associated with a lower Boston Bowel Preparation Scale (BBPS). Knowledge of these factors could identify which patients may benefit from increased pre-procedure guidance or more rigorous bowel preparation. Methods : The charts of consecutive patients undergoing screening or surveillance colonoscopies over a one-year period were reviewed. Cases were defined as BBPS ≤ 5 while controls were patients with BBPS ≥ 6. For each included patient, multiple characteristics were extracted. The chi-square analysis was performed for univariate analysis and a binomial logistic regression model for the multivariable analysis. Results : One thousand and fifty-five colonoscopy reports with BBPS scores were retrieved with 189 cases (BBPS ≤ 5) and 866 controls (BBPS ≥ 6). Cases and controls were similar in age, sex, ethnicity, employment status, and marital status. Compared to patients with adequate bowel preparations, significantly more patients with inadequate bowel preparation had the following characteristics: diabetes, psychiatric illness, American Society of Anesthesiologists class ≥ 3, history of inadequate bowel preparation, active smoker, opioid user, insulin user and Medicaid coverage. On multivariable logistic regression analyses, predictive factors of an inadequate bowel preparation were diabetes, psychiatric illness, opioid use, active tobacco use, history of inadequate bowel preparation, and Medicaid coverage. Conclusion : This large retrospective case-control study identified independent predictive factors of an inadequate bowel preparation. Knowledge of these characteristics may aid both primary care providers and gastroenterologists in identifying patients who could benefit from an extended bowel preparation as well as enhanced education prior to their colonoscopy.